Determination of the hygroscopic equilibrium and isosteric heat of aji chili pepper - Ednilton T. Andrade; Vitor G. Figueira; Luciana P. Teixeira; José H. da S. Taveira; Flávio M. Borém (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study focuses on the determination of the hygroscopic equilibrium and isosteric heat of the aji chili pepper (Capsicum baccatum) under different controlled temperature and relative air humidity conditions. In addition, the objective was to adjust the model among the existing literature models that best represent the isothermal sorption behavior, as well as propose a new model to represent this phenomenon. Having obtained the mathematical models and experimental data, the best model and parameters that represent the hygroscopicity and the isosteric heat satisfactorily was determined. The temperatures used were 30, 55, and 70 °C, with water activity levels from 0.11 to 0.84. The model that best fit the data had a R2 value of 0.97. The integral isosteric heat of sorption for ‘Dedo-de-Moça’ chili pepper within a moisture content from 0.07 to 0.55 (dry basis) ranged from 3641.66 to 2614.38 kJ kg-1.